Evaluation of electrical impedance tomography sensor using internal-external electrodes for small-scale cylindrical root zones. (31st March 2022) - Zhao, Peng-Fei; Fan, Li-Feng; Wang, Yong-Qian; Li, Yang; Wang, Nan; Cheng, Qiang; Wang, Zhong-Yi; Huang, Lan
Highlights: A novel sensor using inner electrodes for plant root zones to improve the resolution. The effects of noise level and conductivity contrast on resolution are analysed. The relatively optimised internal electrode position and measurement strategy. Abstract: To improve the spatial resolution for mapping of small-scale cylindrical plant root zones using electrical impedance tomography, this paper presents a novel sensor structure, where a ring of 16 external electrodes and an inner ring of 8 internal electrodes are included in an electrode layer. To assess the ability of the structure in the electrode plane as well as the effects of measurement noise, conductivity contrast, radial position of internal electrodes, and measurement strategy on its performance, various simulations and experiments were conducted. Results show that the increased noise level or the decreased conductivity contrast will cause the decrease in resolution. Moreover, half the radius of the imaged domain is a good and compromised choice for the radial position of internal electrodes, and the extended adjacent strategy is an available and relatively better choice. Overall, the internal-external electrodes exhibit benefits in improving and uniforming the resolution.